DEUX GROUPES DE COLLEGIENS (ABIDJAN ET TOULOUSE) FACE A DEUX QUESTIONS SUR LA TRANSITIVITE ET L’INTRANSITIVITE EN FRANÇAIS: RECHERCHES SUR LES CONNAISSANCES IMPLICITES ET EXPLICITES DES ADOLESCENTS - ANGELIS, Chiara De; FLOQUET, Oreste (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Two groups of high school students (of Abidjan and Toulouse) answering two questions on transitivity and intransitivity in the French language: a research on teenagers’ implicit and explicit knowledge. By employing the epilinguistic and metalinguistic analysis of a corpus of responses by 170 pre-teenagers from two colleges in Abidjan and Toulouse, we will discuss, first, the concepts of acceptability, grammaticalness and utterability in order to try to determine, as far as possible, on what kind of knowledge and on what type of reasoning they rely on. Secondly, we will discuss the relationship that connects acceptability and age by showing that, contrary to what is expected, the majority of pre-teenagers that we have questioned still ground their responses more in their encyclopedic knowlege than in the formal aspects of the phrase, which is a typical feature of adolescence. REZUMAT. Cum răspund două grupuri de liceeni (din Abidjan și Toulouse) la două întrebări despre tranzitivitate și intranzitivitate în limba franceză: o cercetare asupra cunoștințelor implicite și explicite ale adolescenților. Prin intermediul unei analize epilingvistice și metalingvistice a unui ansamblu de răspunsuri preluate de la 170 de preadolescenți provenind de la două licee din Abidjan și, respectiv, Toulouse, vom discuta, mai întâi, noțiunile de acceptabilitate, gramaticalitate și enunțiabilitate, în încercarea de a stabili, pe cât se poate, care sunt cunoștințele și tipurile de raționamente pe care se bazează acestea. Apoi, vom analiza raportul care se stabilește între acceptabilitate și vârstă, arătând că, contrar așteptărilor noastre, majoritatea preadolescenților chestionați își argumentează încă răspunsurile referindu-se mai degrabă la cunoștințele lor enciclopedice decât la aspectele formale ale frazei, ceea ce reprezintă o trăsătură tipică vârstei adolescente. Cuvinte cheie: acceptabilitate, valență, conștiință metalingvistică, dezvoltare lingvistică.